Direct Comparison Between a Non‐Orographic Gravity Wave Drag Scheme and Constant Level Balloons. Issue 4 (20th February 2023) - Lott, F.; Rani, R.; Podglajen, A.; Codron, F.; Guez, L.; Hertzog, A.; Plougonven, R.
Abstract: The parameterization scheme that represents gravity waves due to convection in LMDz‐6A, the atmospheric components of the IPSL coupled climate model (IPSLCM6), is directly compared to Strateole‐2 balloon observations made in the lower tropical stratosphere from November 2019 to February 2020. The input meteorological fields necessary to run the parameterization offline are extracted from the ERA5 reanalysis and correspond to the instantaneous meteorological conditions found underneath the balloons. In general, we find a fair agreement between measurements of the momentum fluxes due to waves with periods less than 1 hr and the parameterization. The correlation of the daily values between the observations and the results of the parameterization is around 0.4, which is statistically elevated considering that we analyze around 600 days of data and surprisingly good considering that the parameterization has not been tuned: the scheme is just the standard one that helps producing a quasi‐biennial oscillation (QBO) in the IPSLCM6 model. Online simulations also show that the measured values of momentum fluxes are well representative of the zonally and averaged values of momentum fluxes needed in LMDz‐6A to simulate a QBO. The observations also show that longer waves with periods smaller than a day carry about twice as much flux as waves with periods smaller than an hour, which is a challenge since the low period waves that make the difference are potentially in the "gray zone" of most climate models. Plain Language Summary: In most large‐scale atmospheric models, gravity wave (GW) parameterizations are based on well‐understood but simplified theories and parameters which are keyed to reduce systematic errors on the planetary scale winds. In the equatorial regions, the most challenging errors concern the quasi‐biennial oscillation. Although it has never been verified directly, it is expected that the parameterizations tuned this way should transport a realistic amount of momentum flux in both the eastward and westward directions when compared to direct observations. Here, we show that it is the case, to a certain extent, using constant‐level balloon observations at 20 km altitude. The method consists in comparing directly, each day and at the location of the balloon the measured momentum fluxes and the estimation of a GW parameterization using observed values of the large‐scale meteorological conditions of wind, temperature, and precipitation. Key Points: A non‐orographic parameterization tuned to produce a realistic tropical quasi‐biennial oscillation is used to predict in‐situ observations Parameterized gravity waves (GWs) needed in large‐scale models have realistic amplitudes in the tropical lower stratosphere Day‐to‐day variations of the estimated GW momentum fluxes correlate well with observations